2013
DOI: 10.1097/yic.0b013e3283613e4d
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal course of pharmacotherapy in obsessive–compulsive disorder

Abstract: Background Although data fully support the use of serotonin reuptake inhibitors (SRIs) in the treatment of obsessive–compulsive disorder (OCD), investigations on pharmacotherapy discontinuation during the course of OCD are lacking. This 5-year prospective study sought to better understand the long-term course of SRI utilization among individuals with OCD. Methods A total of 252 adult outpatients with Diagnostic and Statistical Manual of Mental Disorders, 4th ed. OCD, treated with medication in the community,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…High doses of SRIs have been consistently associated with greater reductions in OCD symptoms, compared with low doses or placebo, in multiple clinical trials and meta-analyses (37). Similarly, it is well established that relapse rates are high in patients who discontinue their SRI treatment too soon (38)(39)(40). As this is not a randomized controlled study, we are cautious to attribute the observed risk reductions to medication alone.…”
Section: Discussionmentioning
confidence: 97%
“…High doses of SRIs have been consistently associated with greater reductions in OCD symptoms, compared with low doses or placebo, in multiple clinical trials and meta-analyses (37). Similarly, it is well established that relapse rates are high in patients who discontinue their SRI treatment too soon (38)(39)(40). As this is not a randomized controlled study, we are cautious to attribute the observed risk reductions to medication alone.…”
Section: Discussionmentioning
confidence: 97%
“…Trichotillomania occurs with a variety of other disorders such as major depressive (39-65%), anxiety (27-32%), and substance use (15-19%) disorders (11,1617). Where data regarding age of onset are available, trichotillomania generally begins at an earlier age than these co-occurring disorders (18). A study of 894 individuals with trichotillomania found that 6.0% used illegal drugs, 17.7% used tobacco products, and 14.1% used alcohol to relieve negative feelings associated with pulling (2).…”
Section: Screening For Trichotillomaniamentioning
confidence: 99%
“…Urn randomization is used to assign participants [30] in a 1:1 allocation while stratifying treatment assignment on baseline level of OCD severity (cutoff on the YBOCS ≥ 16) [31]. Level of OCD symptomatology at baseline (pre-intervention) is likely a prognostic factor affecting severity and discontinuation outcomes [7] and therefore is controlled during randomization.…”
Section: Study Design and Aimsmentioning
confidence: 99%
“…[3,4] Despite increased recognition of its public health significance, surprisingly little is known about how to optimize long-term treatment of the disorder. Serotonin reuptake inhibitors (SRIs) are the most commonly prescribed medications for OCD [5] with large observational studies estimating lifetime utilization at over 90% in treatment-seeking populations [6,7]. Although widely used and efficacious [810], SRI use long-term is associated with adverse side effects [11–14], as well as problems with adherence and financial burden [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation